Proposição de um método de avaliação de tecnologia de identificação: o caso RFID nas cadeias de carne bovina no Brasil e nos EUA - Ribeiro, Priscilla Cristina Cabral (2009)
Identification technologies such as Radio Frequency Identification RFID and barcode are used in traceability systems. RFID is a promising identification and Information and Communication Technology (ICT) for traceability systems. It can be widely used on various products to control information from the beginning of the process until they reach the ultimate consumer. The objective of this study is to propose a method to evaluate identification technologies, especially RFID, in agro industrial chains and apply it to the beef cattle chain traceability systems. The research methodology used was a qualitative case study using interviews. The evaluation method provided a clear and wide view of the use of RFID in the cattle chain including importance and barriers. The results indicated some RFID advantages such as quickness in the traceability process, information accuracy, and more information stored in the tags among others. The RFID has some disadvantages such as: high costs; absence of international standard for labels; complex integration of this system; consumer privacy; and technical aspects such as broad band limitations for data transmission. In addition, the case studies revealed resistance against the use of RFID.